Implementation of Data-Driven Decision Making in Public Relations Strategy: A Case Study on the Social Media Campaign of TikTok Shop E-Commerce - Yusufi Noviati; Ayun Farichah Khoniaro; Khopsa Chanda Syaputri; Dwi Novaria Misidawati (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
The implementation of Data-Driven Decision Making (DDDM) in Public Relations strategies for TikTok Shop campaigns transforms communication practices from intuition-based approaches to evidence-based strategies. This study highlights four integrated stages: audience mapping using demographic and behavioral data, content formulation based on historical insights, real-time optimization driven by audience responses, and measurable evaluation linking communication performance to business goals. This approach enables more targeted, personalized, and effective communication, while strengthening the strategic role of PR within the competitive TikTok Shop e-commerce ecosystem.